2007
DOI: 10.1254/jphs.fp0060754
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Solifenacin in Patients With Renal Insufficiency

Abstract: Abstract. To evaluate the pharmacokinetics, safety, and tolerability of solifenacin in patients with mild, moderate, or severe renal disease, eighteen patients with renal disease and six healthy volunteers received a single oral dose of solifenacin (10 mg). Pharmacokinetic parameters were assessed from blood samples drawn over a 360-h period. Safety and tolerability were also evaluated. Total mean ± S.D. exposure (ng ⋅ h / mL) to solifenacin in healthy individuals (1190 ± 403) was increased in patients with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…For example, the prescribing information often suggests a renal dosage adjustment based on Cl cr , whereas the pharmacokinetic studies or studies in patients with impaired renal function might report that patients were stratified in the trial based on estimated Cl cr by using the Cockcroft-Gault equation with no weight index specified (e.g., telbivudine) or based on a 24-hour urine collection (solifenacin). 55,56 In such cases, the practitioner has to make a clinical judgment regarding which Cl cr estimation method they will use for dosage adjustment purposes; this most often leads to use of some form of the Cockcroft-Gault equation and involves a weight-based Cockcroft-Gault equation. Having these critical aspects of the pharmacokinetic studies and studies in patients with impaired renal function included in the medical or clinical pharmacology reviews that are available on the FDA Center for Drug Evaluation and Research (CDER) Web site or provided as active Web links within the Webresiding prescribing information would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prescribing information often suggests a renal dosage adjustment based on Cl cr , whereas the pharmacokinetic studies or studies in patients with impaired renal function might report that patients were stratified in the trial based on estimated Cl cr by using the Cockcroft-Gault equation with no weight index specified (e.g., telbivudine) or based on a 24-hour urine collection (solifenacin). 55,56 In such cases, the practitioner has to make a clinical judgment regarding which Cl cr estimation method they will use for dosage adjustment purposes; this most often leads to use of some form of the Cockcroft-Gault equation and involves a weight-based Cockcroft-Gault equation. Having these critical aspects of the pharmacokinetic studies and studies in patients with impaired renal function included in the medical or clinical pharmacology reviews that are available on the FDA Center for Drug Evaluation and Research (CDER) Web site or provided as active Web links within the Webresiding prescribing information would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies describing human systemiclevel and pharmacokinetics of solifenacin had been published [8][9][10][11][12][13]. However, no specific and sufficient details related to the IS used, sample extraction and preparation procedures and MS/MS detection set-up were given [9][10][11][12][13] to allow the reproduction of the used solifenacin analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, no specific and sufficient details related to the IS used, sample extraction and preparation procedures and MS/MS detection set-up were given [9][10][11][12][13] to allow the reproduction of the used solifenacin analytical methods. On the other hand, Mistri et al had some limitations in their pre-analytical protein precipitation step needed to extract solifenacin from its biological matrix [10].…”
Section: Discussionmentioning
confidence: 99%
“…In all studies, solifenacin concentrations were analyzed using liquid chromatography-mass spectrometry with a limit of quantification of 1.38 nmol/l for total solifenacin and 0.55 nmol/l for free solifenacin. A comprehensive description of these studies and results have been reported elsewhere (Krauwinkel et al, 2005;Kuipers et al, 2006;Smulders et al, 2007).…”
Section: Clinicalmentioning
confidence: 99%